2020
DOI: 10.1017/s2040174420000331
|View full text |Cite
|
Sign up to set email alerts
|

Association between early weight gain and later adiposity in Sri Lankan adolescents

Abstract: Early growth pattern is increasingly recognized as a determinant of later obesity. This study aimed to identify the association between weight gain in early life and anthropometry, adiposity, leptin, and fasting insulin levels in adolescence. A cross-sectional study was conducted in 366 school children aged 11–13 years. Weight, height, and waist circumference (WC) were measured. Fat mass (FM) was assessed using bioelectrical impedance analysis. Blood was drawn after a 12-h fast for insulin and leptin assay. Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
2
4
0
Order By: Relevance
“…Similarly, another cohort study showed that a dietary pattern characterized by high sugar and fat foods was related to greater adiposity and obesity risk in childhood [47]. This early postnatal high-energy dietary pattern represents one explanation for accelerated weight gain in early life resulting in higher childhood fat mass [48]. Consistent with these findings, our study also showed that early a postnatal well-nourished nutritional status significantly increases the risk of childhood obesity.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, another cohort study showed that a dietary pattern characterized by high sugar and fat foods was related to greater adiposity and obesity risk in childhood [47]. This early postnatal high-energy dietary pattern represents one explanation for accelerated weight gain in early life resulting in higher childhood fat mass [48]. Consistent with these findings, our study also showed that early a postnatal well-nourished nutritional status significantly increases the risk of childhood obesity.…”
Section: Discussionsupporting
confidence: 89%
“…Accelerated weight gain during mid‐infancy was associated with elevated leptin concentrations, consistent with previous observations in infancy, childhood and adolescence 28,32,33 . Circulating leptin was positively correlated with current BMI or skinfold thickness at age 2 years, consistent with the reported positive correlations of circulating leptin with weight or fat mass at birth, during infancy and childhood 21,28,34 …”
Section: Discussionsupporting
confidence: 89%
“…A previous study concluded that leptin is not only affected by fat mass. It is also affected by reproductive hormones, as the study found higher leptin in adolescents with rapid weight gain during their 0-18 months of life [19].…”
Section: Introductionmentioning
confidence: 89%